Princípio de ius cogens da não discriminação na Carta da ONU: recepção pelo sistema interamericano de direitos humanos - Trindade, Germana Assunção (2019)
This thesis has been developed with the objectives: to analyze how the principle of non-discrimination guaranteed in the Charter of the UN is received by the InterAmerican Human Rights System, and to examine the implications of this reception by the Inter-American Court of Human Rights, regarding safeguards of human beings by the States. The principle of non-discrimination is the only human rights norm guaranteed in the Charter of the UN and is also expressly provided for in the American Convention. The decisions of the Inter-American Court of Human Rights, on the other hand, recognize the principle of non-discrimination as having the ius cogens attribute. The Court materializes in its decisions, the primacy of the non-discrimination principle, in lieu of of its characteristic of ius cogens, over all acts of the State or of individuals, whenever individuals perform them under the tolerance, acquiescence or negligence of the state. This results in the Court adopting various sanctions (measures of satisfaction, restitution, rehabilitation and guarantees of non-repetition, as well as indemnities and pecuniary compensations), which go far beyond the compensation of the victim when the principle of ius cogens of non-discrimination is violated. In the decisions analyzed, the Court does not clearly and robustly demonstrate that this principle meets the requirements contained in art. 53 of the American Convention, nor does it impose the penalty of nullity contained in that article on the discriminatory act or rule. However, it is concluded that the decisions of the Court are effective in modifying the way States act and, consequently, in the protection, without discrimination, of human beings.